Object Recognition and Conversational AI in Real-World Contexts: Enhancing Museum Experiences through Interactive Systems - Ortiz, Adrián; Illana, Álvaro; Salas, Marta (Street Art & Urban Creativity, 2025)
This project addresses the challenge of improving museum visitors’ experiences by moving beyond static and traditional information access methods. It presents the design and validation of an interactive system that combines real time object detection with a Retrieval Augmented Generation pipeline to offer a context-aware, personalized and immersive conversational guide. The results verify an accurate spatial and conversational understanding, and a significant improvement in the veracity and relevance of generated responses in comparison with standard LLM responses. This project demonstrates the system’s potential to offer a dynamic and attractive access to cultural heritage.